The surface structure of flame-annealed Au(100) in aqueous solution: An STM study - Batina, Nikola; Dakkouri, Andrea S.; Kolb, Dieter M. (Journal of Electroanalytical Chemistry, 1994)
The initial structure of flame-annealed Au(100) surfaces has been studied in air and in 0.1 M HSO by scanning tunnelling microscopy (STM). It is shown that before, during and after contact with the electrolyte, at potentials sufficiently negative to prevent specific adsorption of anions, the flame-annealed Au(100) surface is reconstructed into exactly the same "hex" form as a surface which has been prepared by annealing in ultrahigh vacuum (UHV). However, the quality of the reconstructed surface depends sensitively on the sample preparation and on the experimental conditions of the flame-annealing procedure. The influence of the cooling procedure after flame annealing on the initial surface structure of the Au(100) electrode is demonstrated and briefly discussed in the light of results published previously. © 1994.